Comparative Developmental Toxicity of a Comprehensive Suite of Polycyclic Aromatic Hydrocarbons - Geier, Mitra C. (Arch Toxicol, 2017)
Polycyclic aromatic hydrocarbons (PAHs) are widespread environmental contaminants that occur in complex mixtures. Several PAHs are known or suspected mutagens and/or carcinogens, but developmental toxicity data is lacking for PAHs, particularly their oxygenated and nitrated derivatives. Such data is necessary to understand and predict the toxicity of environmental mixtures. 123 PAHs were assessed for morphological and neurobehavioral effects for a range of concentrations between 0.1 and 50 μM, using a high-throughput early life stage zebrafish assay, including 33 parent, 22 nitrated, 17 oxygenated, 19 hydroxylated, 14 methylated, 16 heterocyclic, and 2 aminated PAHs. Additionally, each PAH was evaluated for AHR activation, by assessing CYP1A protein expression using whole animal immunohistochemistry (IHC). Responses to PAHs varied in a structurally-dependent manner. High-molecular weight PAHs were significantly more developmentally toxic than the low-molecular weight PAHs, and CYP1A expression was detected in 5 distinct tissues, including vasculature, liver, skin, neuromasts and yolk.